DINAMIKA MAKNA SIMBOLIS ORNAMEN RUMAH ADAT MALIGE DI KERATON BUTON KECAMATAN MURHUM KOTA BAUBAU - Zainab Jasrub; Wa Ode Sifatu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to determine the dynamics of the meaning contained in Malige House ornaments used in Buton Palace. The theory used to read research data is symbol theory proposed by Geertz and uses ethnographic methods. Data collection is done through observation and in-depth interviews. The results of this study indicate that the placement of traditional Malige house ornaments in the Buton community has undergone a shift. If it was first placed on a roof, now it is placed on the roof of a private house, even a house fence, both from the descendants of nobility and ordinary people. In connection with this, the Butonese also have different interpretations, regarding the meaning of bosubosu and nanasi ornaments. Some interpret it as a place of water and some interpret it as earrings. This happened because there were no guidelines about the meaning of the symbol of the Malige traditional house. Ornaments in Geertz's theory are equivalent to far-reaching experiences with regard to social stratification. But in his explanation, Geertz did not speak of the context of ornaments installed based on the descendants of community members who used these ornaments. Keywords: dynamics, meaning, symbol, ornaments, malige.